Inorganic carbon enrichment does not increase production of polyunsaturated aldehydes in a pelagic and benthic diatom. - Jeremy P Johnson; Karin L Lemkau; Ian W Parker; Michael Brady Olson (PLoS ONE)
Seasonal upwelling in coastal environments supports high primary production by increasing concentrations of inorganic nutrients in the euphotic zone. Diatoms typically dominate planktonic primary production and community composition during seasonal upwelling, especially in temperate ecosystems. Some diatoms elevate their competitive fitness by producing polyunsaturated aldehydes (PUAs). These phytochemicals act to reduce the fecundity of their grazers by reducing sperm motility, lowering egg production and viability, and delaying embryo development, reducing diatom consumptive pressure. While research into the mechanisms driving PUA production includes bottom-up factors (i.e., nutrient availability), few studies have explored how dissolved carbon dioxide (pCO2) concentration affects PUA production. In this study, we analyzed the production of bioactive PUAs (2,4-heptadienal, 2,4-octadienal, and 2,4-decadienal) in two diatom species found in the Salish Sea, an inland sea of the North Pacific ecosystem, under varying pCO2 concentrations that are experienced during seasonal upwelling events. We found that elevated pCO2 concentration caused an increase in carbon uptake in the diatoms, but did not lead to more PUA production, and at times caused a decrease in production. Our results suggest that carbon enrichment does not elevate the chemically defensive capabilities of diatoms by way of elevated PUA production.